Modeling and control of a nonlinear half-vehicle suspension system: a hybrid fuzzy logic approach - Demir, Ozgur; Keskin, Ilknur; Cetin, Saban (SPRINGER, 2012)
Modeling and control of vehicle suspension system are high noteworthy from safety to comfort. In this paper, an analytical nonlinear half-vehicle model which is included quadratic tire stiffness, cubic suspension stiffness, and coulomb friction is derived based on fundamental physics. A hybrid fuzzy logic approach which combines fuzzy logic and PID controllers is designed for reducing the vibration levels of passenger seat and vehicle body. Performances of designed controllers have been evaluated by numerical simulations. Comparisons with classical PID control, Fuzzy Logic Control (FLC) and Hybrid Fuzzy-PID control (HFPID) have also been provided. Results of numerical simulations are evaluated in terms of time histories of displacement and acceleration responses and ride index comparison. A good performance for the Hybrid Fuzzy-PID controller with coupled rules (HFPIDCR) is achieved in simulation studies despite the nonlinearities.
Keywords: Nonlinear model; Coulomb friction; Half vehicle; Hybrid fuzzy PID; Active suspension system; GAIN-SCHEDULING CONTROLLER; ACTIVE SUSPENSION; SEAT VIBRATIONS; SHOCK ABSORBER; ROAD VEHICLES; OPTIMIZATION; SIMULATION; DESIGN; SENSITIVITY; Engineering; Mechanics